An in-situ synthesized high-voltage resistant gel polymer electrolyte

Through the in-situ synthesis of the crosslinking reaction between the tetramer crosslinking agent and dienyl monomer, a stable crosslinking network is formed, which solves the problems of narrow electrochemical windows and poor interface compatibility of traditional power battery electrolytes, and realizes lithium ions The high ionic conductivity and electrochemical stability of the battery simplifies the preparation process and reduces energy consumption.

CN115275334BInactive Publication Date: 2024-12-24BEIJING INST OF TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202210397713.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-15
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The liquid electrolytes of traditional power batteries have problems such as narrow electrochemical window, fluidity risks, safety hazards and poor interface compatibility. The existing gel polymer electrolytes have low electrochemical windows and poor circulation performance, and the preparation method is cumbersome and capable. High consumption.

Method used

Using in-situ synthesis method, a cross-linking reaction is carried out using tetramer cross-linking agent and dienyl monomer in an atmosphere with low light-proof oxygen and water content to form a stable cross-linking network, which improves the transmission efficiency of lithium ions and passes through In situ polymerization method infiltrates the surface of the positive electrode to form a gel polymer electrolyte, improving the interface compatibility between the electrolyte and the positive electrode.

Benefits of technology

The high ion conductivity, lithium ion migration number and electrochemical window width of lithium ion batteries at room temperature are achieved, which improves the electrochemical stability and cyclic performance of the battery, simplifies the preparation process, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275334B_ABST
    Figure CN115275334B_ABST
Patent Text Reader

Abstract

The present invention relates to an in-situ synthesized high-voltage resistant gel polymer electrolyte, belonging to the technical field of gel polymer electrolytes. The electrolyte is prepared by the following method: in a light-proof protective gas atmosphere with oxygen and water contents less than 1 ppm, PETT and divinyl adipate are added to an electrolyte in a substance ratio of 1: (1-4) to obtain a mixed solution a, wherein the concentration of PETT is (0.2-5) mol / L, and then a free radical polymerization photoinitiator is added and mixed to obtain a mixed solution b, and bubbles in the mixed solution b are removed to obtain a precursor solution; the precursor solution is used to infiltrate the positive electrode material in the positive electrode for 0.5h-2h, and then visible light is used for irradiation for 0.2h-1h to obtain the electrolyte on the positive electrode. The electrolyte has good ionic conductivity and lithium ion migration number, and has a wide electrochemical window, and has good interface compatibility with the positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an in-situ synthesized high-voltage resistant gel polymer electrolyte, belonging to the technical field of gel polymer electrolytes. Background Art

[0002] New energy vehicles use power batteries as their energy source, which are environmentally friendly and have low carbon emission reduction characteristics. Traditional power batteries use liquid electrolytes, which have a narrow electrochemical window (about 4.3V) and are difficult to match with high-voltage positive electrode materials with higher capacity density, which restricts the mileage problem. On the other hand, the morphological characteristics of the fluidity of liquid electrolytes have leakage risks; the organic solvents used are flammable liquids; there is no mechanical strength, and the lithium dendrites generated by side reactions with the negative electrode will pierce the diaphragm, causing internal short circuits and local high temperatures, causing fires and other accidents, all of which make traditional power batteries have high safety risks. Therefore, researchers turned their attention to solid electrolyte materials.

[0003] Solid electrolyte materials are non-flowable and have a certain mechanical strength. They can resist the penetration of lithium dendrites to a certain extent, or fundamentally inhibit the growth of lithium dendrites, providing a safe and convenient guarantee. Solid electrolytes are divided into all-solid electrolytes and quasi-solid electrolytes. All-solid electrolytes are mainly composed of oxides, sulfides, polymers, etc., which do not add any liquid components and have strong mechanical properties, but the ionic conductivity level at room temperature is low (about 10 -5 S / cm), and has a large interface compatibility problem with the solid-solid contact between the positive and negative electrodes, and cannot meet the current usage requirements. Quasi-solid electrolytes mainly refer to gel polymer electrolyte systems. By adding plasticizers to polymers to form a gel state, lithium ions can be conducted more efficiently in the amorphous regions, greatly improving the ionic conductivity at room temperature.

[0004] The gel polymer electrolytes reported so far are mainly based on polymers such as polyvinylidene fluoride (PVDF) and its copolymers, poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-co-HFP)), polyethylene oxide (PEO) or polyacrylonitrile (PAN). However, the electrochemical window of these electrolytes is low, basically distributed at around 4.5V, which cannot match the high-voltage positive electrode materials in lithium-ion batteries, and the cycle performance at room temperature is poor. In addition, the preparation methods of these gel polymer electrolytes mainly adopt non-in-situ preparation methods such as solution casting film formation, phase separation, phase inversion or electrospinning, and also need to be prepared by thermal initiation or ultraviolet light initiation polymerization reaction. Not only are the synthesis steps cumbersome, but also require additional energy consumption. In addition, there is also the problem of poor interface compatibility between the electrolyte and the positive electrode, which leads to poor performance in charge and discharge capacity. Summary of the invention

[0005] In view of this, the object of the present invention is to provide an in-situ synthesized high-voltage resistant gel polymer electrolyte, which has good ionic conductivity and lithium ion migration number at room temperature and a wide electrochemical window. By in-situ polymerization, the electrolyte and the positive electrode have good interface compatibility, and the prepared electrolyte has good electrochemical stability and cycle stability.

[0006] To achieve the purpose of the present invention, the following technical solutions are provided.

[0007] An in-situ synthesized high-voltage resistant gel polymer electrolyte, wherein the electrolyte is prepared by the following method:

[0008] (1) Preparation of precursor solution:

[0009] In a light-proof protective gas atmosphere in which oxygen and water contents are both less than 1 ppm, a tetrathiol crosslinking agent and a diene monomer are added to an electrolyte to obtain a mixed solution a, and then a free radical polymerization photoinitiator is added and mixed uniformly to obtain a mixed solution b, and bubbles in the mixed solution b are removed by vacuuming to obtain a precursor solution;

[0010] (2) Preparation of gel polymer electrolyte by in situ synthesis:

[0011] In a light-proof protective gas atmosphere with oxygen and water content less than 1 ppm, the precursor solution is added dropwise to the surface of the positive electrode material in the positive electrode for infiltration, the infiltration time is 0.5 h to 2 h, and then irradiated with visible light for 0.2 h to 1 h to obtain a fully polymerized gel polymer electrolyte on the positive electrode;

[0012] The protective gas is an inert gas or nitrogen;

[0013] The tetramercapto crosslinking agent is pentaerythritol tetrakis (3-mercaptopropionate) (PETT);

[0014] The diene monomer is divinyl adipate (Ester);

[0015] The electrolyte is an electrolyte used in lithium-ion batteries in the prior art, and is composed of a lithium salt and an organic solvent. The lithium salt is a lithium salt used in lithium-ion batteries in the prior art; the organic solvent is an organic solvent used in electrolytes in lithium-ion batteries in the prior art;

[0016] The molar ratio of the tetramercapto crosslinking agent to the diene monomer is 1:(1-4);

[0017] The mass fraction of the photoinitiator is 1% to 10% based on the sum of the mass of the tetramercapto crosslinking agent and the diene monomer as 100%;

[0018] In the mixed solution a, the concentration of the tetrathiol crosslinking agent is 0.2 mol / L to 5 mol / L.

[0019] Preferably, the molar ratio of the tetramercapto crosslinking agent to the diene monomer is 1:(1.5-3.5).

[0020] Preferably, in the mixed solution a, the concentration of the tetrathiol crosslinking agent is 0.5 mol / L.

[0021] Preferably, the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0022] Preferably, based on the sum of the mass of the tetramercapto crosslinking agent and the diene monomer being 100%, the mass fraction of the photoinitiator is 3%.

[0023] Preferably, the lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or more thereof.

[0024] Preferably, the organic solvent is one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC) and ethyl propyl carbonate (EPC).

[0025] More preferably, the lithium salt is LiPF 6 , LiBF 4 and one of LiTFSI; the organic solvent is composed of two of EC, DMC, DEC, DPC, EMC, MPC and EPC in a volume ratio of 1:1; and the concentration of the lithium salt in the electrolyte is 1 mol / L.

[0026] Preferably, the positive electrode material is lithium iron phosphate (LiFePO 4 ), lithium cobalt oxide (LiCoO 2 ), nickel-cobalt-manganese ternary material (NCM) or nickel-cobalt-aluminum ternary material (NCA).

[0027] More preferably, the positive electrode material is LiFePO 4 .

[0028] Preferably, the specific operation of removing bubbles in the mixed solution b by vacuuming is: vacuuming the mixed solution b 2 to 5 times, and vacuuming to -0.08 MPa to -0.1 MPa each time.

[0029] Beneficial Effects

[0030] 1. The present invention provides an in-situ synthesized high-voltage resistant gel polymer electrolyte, wherein the electrolyte is cross-linked by a specific tetrathiol cross-linking agent and a diene monomer during an in-situ reaction, and under the reaction conditions of the amount ratio of the tetrathiol cross-linking agent and the diene monomer, the concentration of the tetrathiol cross-linking agent, and the illumination time, a stable cross-linked network is formed, and the network structure can effectively lock the electrolyte, generate an amorphous region, and improve the transmission efficiency of lithium ions, thereby having good ionic conductivity and lithium ion migration number at room temperature, and improving the electrochemical window of the electrolyte. In addition, the in-situ synthesis method is adopted to improve the interface compatibility between the electrolyte and the positive electrode, and thus the conductivity and cycle performance of the battery at room temperature can also be improved. The gel polymer electrolyte synthesized in situ by the present invention has a wide electrochemical window, indicating that the electrolyte has good electrochemical stability, and thus has good rate performance and cycle performance. The gel polymer electrolyte described in the present invention is applied to a lithium ion battery, which can make the lithium ion battery have good ionic conductivity and lithium ion migration number at room temperature, and show high electrochemical stability and cycle stability.

[0031] 2. The present invention provides an in-situ synthesized high-voltage resistant gel polymer electrolyte, which can trigger the polymerization reaction of the tetrathiol crosslinking agent and the diene monomer under visible light, and finally obtain an independently supported electrolyte membrane. No special light source or high-temperature heating is required, and no supporting material is required. The preparation method simplifies the synthesis steps, reduces the synthesis energy consumption, and is low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is the infrared analysis spectrum of Example 1 and Example 2.

[0033] Figure 2 It is the XRD diagram of Example 1 and Example 2.

[0034] Figure 3 It is the TGA chart of Example 1 and Example 2.

[0035] Figure 4 2 are the conductivity diagrams of Example 1 and Example 2.

[0036] Figure 5 This is the ion migration number measurement curve of Example 1 at room temperature.

[0037] Figure 6 This is the ion migration number measurement curve of Example 2 at room temperature.

[0038] Figure 7 These are the electrochemical window test curves of Example 1, Example 2 and Comparative Example 2.

[0039] Figure 8It is a cycle test curve of the batteries assembled in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 at a current density of 0.2C.

[0040] Fig. 9 It is a charge and discharge curve diagram of the LFP battery assembled in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 at a current density of 0.2C.

[0041] Fig.10 It is a rate performance diagram of Example 2 at 0.1C, 0.2C, 0.5C, 1C, 0.5C, 0.2C and 0.1C. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels or prepared according to literature unless otherwise specified.

[0043] In the following embodiments, comparative examples and test examples:

[0044] The infrared spectrum test was performed using an iS10 Fourier transform infrared spectrometer from Nicolet Instruments, Inc., USA.

[0045] The X-ray diffraction (XRD) test was performed using a Rigaku Ultima IV-185 X-ray diffractometer from Japan.

[0046] The thermogravimetric analysis (TGA) test was performed using a STA449F3 synchronous thermal analyzer produced by NETZSCH Instrument Manufacturing Co., Ltd. of Germany.

[0047] The AC impedance test was conducted using the CHI660E electrochemical workstation of Shanghai Chenhua Instrument Co., Ltd. (hereinafter referred to as "Shanghai Chenhua"), and the test conditions were: test voltage was 0V, test frequency range: 0.1Hz~100kHz, amplitude was 5mV; and the ionic conductivity was calculated according to formula (1-1):

[0048]

[0049] Where: δ is the ionic conductivity, L is the electrolyte thickness, R is the electrolyte body resistance, and S is the working electrode area.

[0050] The lithium ion migration number The test was carried out using Shanghai Chenhua CHI660E electrochemical workstation and chronoamperometry. Specifically, the test was first carried out under the conditions of amplitude (ΔV) of 1mV and scan time of 5000s to obtain the initial current (I 0 ) and steady-state current (I s); before and after the chronoamperometric test, the battery to be tested is tested according to the above-mentioned AC impedance test method to obtain the initial state of the body resistance of the battery to be tested Steady-state bulk resistance Initial interface impedance and the steady-state interfacial impedance The lithium ion migration number is calculated by formula (1-2):

[0051]

[0052] The electrochemical window test method is: linear scanning is performed using Shanghai Chenhua's CHI660E electrochemical workstation, and the test conditions are: the starting voltage is the open circuit voltage, the ending voltage is 5.5V, and the scanning rate is 1mV / s.

[0053] Constant current charge and discharge cycle test: The battery to be tested is tested using the CT2001A LAND battery test system of Wuhan Landian Electronics Co., Ltd. The test conditions are: charge and discharge voltage range: 2.75V~4.3V (vs.Li / Li + ), the test temperature is 30℃.

[0054] The batteries involved were assembled in a glove box filled with argon, and the oxygen and water content in the glove box were less than 1 ppm.

[0055] Fluorescent lamps are used as the light source of visible light, and the wavelength range is 400nm to 700nm.

[0056] Example 1

[0057] (1) Preparation of LEP positive electrode:

[0058] In an environment with an air humidity of less than 30%, 0.16g of LiFePO 4 and 0.02g of acetylene black are placed in an agate mortar and ground for 20min, then 0.4g of a binder is added and ground for 10min to obtain a slurry, and the slurry is evenly coated on an aluminum foil with a scraper. The thickness of the slurry is 125μm. The aluminum foil coated with the slurry is dried at 80°C for 24h and punched into a disc with a diameter of 11mm, which is the LFP positive electrode; the binder is polyvinylidene fluoride (PVDF) dissolved in N-methylpyrrolidone (NMP), and the mass fraction of PVDF is 5% based on the sum of the masses of PVDF and NMP as 100%. The PVDF is PVDF with model HSV-900 produced by Shanghai Songjing New Energy Technology Co., Ltd.

[0059] (2) Preparation of precursor solution:

[0060] In a glove box filled with argon gas, where the oxygen and water contents in the glove box were both less than 1 ppm, 1.2217 g of PETT and 0.7433 g of Ester were added to 5 mL of electrolyte to obtain a mixed solution a, and then phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the mixed solution a as a photoinitiator, and stirred for 1 min to mix evenly to obtain a mixed solution b. After 3 times of vacuuming, each time the vacuum was evacuated to -0.1 MPa to eliminate bubbles in the mixed solution b, a precursor solution was obtained, which was recorded as PE1.5 precursor solution; wherein the molar ratio of PETT and Ester is 1:1.5; in the mixed solution a, the concentration of PETT is 0.5 mol / L; the lithium salt in the electrolyte is LiTFSI, the organic solvent in the electrolyte is composed of EC and DEC in a volume ratio of 1:1, and the concentration of LiTFSI in the electrolyte is 1 mol / L; based on the sum of the masses of PETT and divinyl adipate as 100%, the mass fraction of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide is 3%.

[0061] (3) Preparation of gel polymer electrolyte by in situ synthesis:

[0062] In a glove box filled with argon gas, where the oxygen and water contents in the glove box are both less than 1 ppm, 250 μL of PE1.5 precursor solution is directly added dropwise to the positive electrode material in the LFP positive electrode prepared in step (1), and then immersed in the dark for 0.5 h. After irradiation with a fluorescent lamp for 1 h, a completely polymerized gel polymer electrolyte is obtained on the positive electrode, with an average thickness of 514 μm. The electrolyte is recorded as PE1.5 electrolyte, and the material integrating the positive electrode and the electrolyte is recorded as LFP-PE1.5.

[0063] Example 2

[0064] (1) Preparation of LEP positive electrode: This step is the same as step (1) of Example 1.

[0065] (2) Preparation of precursor solution:

[0066] In a glove box filled with argon gas, and the oxygen and water contents in the glove box are both less than 1 ppm, 1.2217 g of PETT and 1.7344 g of Ester are added to 5 mL of electrolyte to obtain a mixed solution a, and then phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is added to the mixed solution a as a photoinitiator, and stirred for 2 minutes to mix evenly to obtain a mixed solution b. After 4 times of vacuuming, each time the vacuum is evacuated to -0.1 MPa to eliminate bubbles in the mixed solution b, a precursor solution is obtained, which is recorded as PE3.5 precursor solution; wherein the molar ratio of PETT and Ester is 1:3.5; in the mixed solution a, the concentration of PETT is 0.5 mol / L; the lithium salt in the electrolyte is LiTFSI, the organic solvent in the electrolyte is composed of EC and DEC in a volume ratio of 1:1, and the concentration of LiTFSI in the electrolyte is 1 mol / L; based on the sum of the masses of PETT and divinyl adipate as 100%, the mass fraction of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide is 3%.

[0067] (3) Preparation of gel polymer electrolyte by in situ synthesis:

[0068] In a glove box filled with argon gas, where the oxygen and water contents in the glove box are both less than 1 ppm, 250 μL of PE3.5 precursor solution is directly added dropwise to the positive electrode material in the LFP positive electrode prepared in step (1), and then immersed in the dark for 2 h and irradiated with a fluorescent lamp for 0.2 h. A completely polymerized gel polymer electrolyte is obtained on the positive electrode, and its average thickness is 217 μm. The electrolyte is recorded as PE3.5 electrolyte, and the material integrating the positive electrode and the electrolyte is recorded as LFP-PE3.5.

[0069] Comparative Example 1

[0070] A non-in-situ synthesized gel polymer electrolyte is prepared according to the following method:

[0071] (1) Preparation of LEP positive electrode: This step is the same as step (1) of Example 1.

[0072] (2) Preparation of precursor solution: This step is the same as step (2) of Example 2, and a PE3.5 precursor solution is obtained;

[0073] (3) In a glove box filled with argon gas, where the oxygen and water contents in the glove box were both less than 1 ppm, the electrolyte was prepared by a natural casting method. 5 mL of the PE3.5 precursor solution was directly poured onto a mold and cast evenly. The mold was irradiated with a fluorescent lamp for 0.5 h to obtain a completely polymerized gel polymer electrolyte. The electrolyte was demolded and punched into a disc with a diameter of 19 mm, which was recorded as a non-in-situ PE electrolyte.

[0074] Comparative Example 2

[0075] A liquid electrolyte is prepared according to the following method:

[0076] (1) Preparation of LEP positive electrode: This step is the same as step (1) of Example 1.

[0077] (2) Preparation of LE electrolyte: In a glove box filled with argon gas with oxygen and water contents less than 1 ppm, 1.4054 g of LiTFSI was dissolved in 5 mL of an organic solvent and stirred for 15 min to mix well to obtain a LE electrolyte; wherein the organic solvent was composed of EC and DEC in a volume ratio of 1:1.

[0078] Test Example 1

[0079] The PE1.5 electrolyte and LFP-PE1.5 prepared in Example 1, and the PE3.5 electrolyte and LFP-PE3.5 prepared in Example 2 were tested as follows:

[0080] (1) PE1.5 electrolyte, PE3.5 electrolyte, PETT and Ester were tested by infrared spectroscopy respectively. The test results are as follows Figure 1 As shown, PE1.5 electrolyte and PE3.5 electrolyte have a peak at 1050 cm -1 The characteristic peak of CSC appeared at 2570 cm -1 The characteristic peak of thiol at 1640 cm -1 The characteristic peak at is a C=C structure. Compared with the infrared spectrum of Ester, the intensity of the characteristic peaks of PE1.5 electrolyte and PE3.5 electrolyte at this location is weakened, indicating that Ester participates in the reaction but still has excess residue; in summary, PETT and Ester undergo a cross-linking polymerization reaction to obtain the PE1.5 electrolyte of Example 1 and the PE3.5 electrolyte of Example 2.

[0081] (2) X-ray diffraction (XRD) tests were performed on PE1.5 electrolyte and PE3.5 electrolyte. The test results are shown in Figure 2 Both have broadened bun peaks at low angles and severe burr phenomenon, indicating that the degree of crystallinity is very low and the amorphous region is dominant. It can be seen that both PE1.5 electrolyte and PE3.5 electrolyte can promote the efficient transmission of lithium ions at room temperature.

[0082] (3) TGA test was performed on PE1.5 electrolyte and PE3.5 electrolyte. The test results are shown in Figure 3 , both began to decompose at a temperature of about 146°C, indicating that both have good thermal stability.

[0083] (4) PE1.5 electrolyte and PE3.5 electrolyte were assembled into SS / PE1.5 / SS battery and SS / PE3.5 / SS battery respectively, that is, the positive and negative electrodes of the battery were both stainless steel sheets, referred to as SS, and an electrolyte was provided between the positive and negative electrodes. Specifically, PE1.5 electrolyte or PE3.5 electrolyte was directly synthesized in situ on the stainless steel sheet, and then assembled with another stainless steel sheet in a CR2032 button battery to obtain the corresponding battery; then the AC impedance of the two batteries was measured, and the test results are shown in Figure 4 , it can be seen that the body resistance R of PE1.5 electrolyte is 25.5Ω, and the body resistance R of PE3.5 electrolyte is 44.5Ω. According to formula (1-1), the ionic conductivity of PE1.5 electrolyte at room temperature is 1.0×10 -3 S / cm, the ionic conductivity of PE3.5 electrolyte at room temperature is 4.8×10 -4 S / cm, indicating that both PE1.5 electrolyte and PE3.5 electrolyte have good ionic conductivity and can reach the level of practical application.

[0084] (5) The PE1.5 electrolyte and the PE3.5 electrolyte are respectively assembled into Li / PE1.5 / Li batteries and Li / PE3.5 / Li batteries, that is, the positive and negative electrodes of the batteries are both metal lithium sheets, referred to as Li, and an electrolyte is provided between the positive and negative electrodes. Specifically, the PE1.5 electrolyte or the PE3.5 electrolyte is directly synthesized in situ on the metal lithium sheet, and then assembled with another metal lithium sheet in a CR2032 button battery to obtain the corresponding battery; then the lithium ion migration numbers of the two batteries are measured, and the test results are shown in FIG. Figure 5 and Figure 6 According to formula (1-2), the lithium ion migration number of PE1.5 electrolyte at room temperature is 0.46, and the lithium ion migration number of PE3.5 electrolyte at room temperature is 0.45. It can be seen that the lithium ion migration numbers of PE1.5 electrolyte and PE3.5 electrolyte have reached a relatively high level, that is, the liquid electrolyte level, and have good application potential.

[0085] Test Example 2

[0086] The PE1.5 electrolyte prepared in Example 1, the PE3.5 electrolyte prepared in Example 2 and the LE electrolyte prepared in Comparative Example 2 were assembled into Li / PE1.5 / SS batteries, Li / PE3.5 / SS batteries and Li / LE / SS batteries, that is, the positive electrode of the battery was a stainless steel sheet (abbreviated as SS), the negative electrode was a metal lithium sheet (abbreviated as Li), and an electrolyte or electrolyte was provided between the positive and negative electrodes. Specifically, the PE1.5 electrolyte or PE3.5 electrolyte was directly synthesized in situ on the stainless steel sheet, and then assembled with the metal lithium sheet in a CR2025 button battery, respectively, to obtain the Li / PE1.5 / SS battery and the Li / PE3.5 / SS battery; Celgard 2500 diaphragm was stacked on the metal lithium sheet and the stainless steel sheet, and 80 μL of LE electrolyte was dripped, and assembled in a CR2025 button battery to obtain a Li / LE / SS battery.

[0087] The electrochemical windows of the three batteries were then measured, and the test results are shown in Figure 7 It can be seen that the electrochemical window of Li / PE1.5 / SS battery can reach 4.75V, the electrochemical window of Li / PE3.5 / SS battery can reach 5.1V, and the electrochemical window of Li / LE / SS battery can only reach 4.21V, which is much lower than that of Li / PE1.5 / SS battery and Li / PE3.5 / SS battery. It also further shows that both PE1.5 electrolyte and PE3.5 electrolyte have higher electrochemical windows and stronger electrochemical stability.

[0088] Test Example 3

[0089] The LFP-PE1.5 prepared in Example 1 and a negative electrode metal lithium sheet were assembled into a CR2032 button battery to obtain a Li / PE1.5 / LFP battery.

[0090] The LFP-PE3.5 prepared in Example 2 and a negative electrode metal lithium sheet were assembled into a CR2032 button battery to obtain a Li / PE3.5 / LFP battery.

[0091] The non-in-situ PE electrolyte prepared in Comparative Example 1 was assembled in a CR2032 button cell in a stacked manner with an LFP positive electrode and a metal lithium sheet negative electrode to obtain a Li / non-in-situ PE / LFP battery, wherein the preparation method of the LFP positive electrode was the same as step (1) in Example 1.

[0092] The LE electrolyte prepared in Comparative Example 2 was used to assemble a Li / LE / LFP battery, specifically, Celgard 2500 separators were stacked between the positive and negative electrodes, and 80 μL of LE electrolyte was added dropwise, wherein the positive electrode was an LFP positive electrode, the preparation method was the same as step (1) in Example 1, and the negative electrode was a metal lithium sheet.

[0093] Then, the Li / PE1.5 / LFP battery, Li / PE3.5 / LFP battery, Li / ex situ PE / LFP battery and Li / LE / LFP battery were subjected to constant rate charge and discharge cycle tests at 30°C and 0.2C rate, with a voltage range of 2.7V to 3.8V. The test results are shown in Figure 8 The first week charge and discharge curves of the above four batteries are as follows: Fig. 9 As shown, according to Figure 8 and Fig. 9 It can be seen that after activation, the first-week capacity of the Li / PE1.5 / LFP battery is 151.7 mAh / g. After 300 cycles of charge and discharge, its capacity retention rate is 94.6%, with an average weekly decay of 0.18‰, indicating that the battery has good cycle stability.

[0094] The first-week capacity of the Li / PE3.5 / LFP battery is 158.9mAh / g. It can be charged and discharged for up to 450 weeks, with a capacity retention rate of 90.0% and an average weekly decay of 0.22‰, indicating that the battery has outstanding cycle performance. Further rate testing of the Li / PE3.5 / LFP battery is performed, and the test results are as follows: Fig.10 At 0.1C, the capacity of the battery can reach 161.5mAh / g. After high current charge and discharge, the battery still has a capacity of 160.1mAh / g at a rate of 0.1C, indicating that it has good rate performance.

[0095] The first-week capacity of the Li / ex-situ PE / LFP battery was 132.1 mAh / g, and the cycle lasted only 148 weeks, with a capacity retention rate of 96.9% and an average weekly decay of 0.20‰; its cycle performance was poorer than that of the PE3.5 electrolyte synthesized in situ in the same proportion in Example 2, which was attributed to the poor interface compatibility between the ex-situ synthesized electrolyte and the positive electrode, the loose contact, which hindered the transmission of lithium ions.

[0096] The capacity of the Li / LE / LFP battery in the first week was 154.2mAh / g, which was due to the good wettability of the liquid electrolyte to the positive electrode. However, after 232 weeks, the capacity of the battery began to decay significantly, and the charge and discharge cycle was only carried out for 239 weeks. The capacity retention rate of the battery in 230 weeks was 87.4%, with an average weekly decay of 0.55‰, indicating that the cycle stability of the battery is far inferior to that of the battery assembled with the electrolyte prepared in Examples 1 and 2.

[0097] It can be seen from the test results of Test Examples 2 and 3 that the gel polymer electrolyte prepared in Examples 1 and 2 is used in lithium-ion batteries, which can significantly improve the compatibility between the quasi-solid electrolyte and the positive electrode, has good ionic conductivity and lithium ion migration number at room temperature, and exhibits high electrochemical stability and cycle stability.

[0098] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.

Claims

1. An in-situ synthesized high-voltage resistant gel polymer electrolyte, characterized in that: The electrolyte is prepared by the following method: (1) in a light-proof protective gas atmosphere in which oxygen and water contents are both less than 1 ppm, a tetrathiol crosslinking agent and a diene monomer are added to an electrolyte to obtain a mixed solution a, and then a free radical polymerization photoinitiator is added and mixed uniformly to obtain a mixed solution b, and bubbles in the mixed solution b are removed by vacuuming to obtain a precursor solution; (2) in a light-proof protective gas atmosphere with oxygen and water content less than 1 ppm, dropwise adding the precursor solution to the surface of the positive electrode material in the positive electrode for infiltration, the infiltration time is 0.5 h to 2 h, and then irradiating with visible light for 0.2 h to 1 h to obtain a fully polymerized gel polymer electrolyte on the positive electrode; The protective gas is an inert gas or nitrogen; The tetramercapto crosslinking agent is pentaerythritol tetrakis (3-mercaptopropionate); The diene monomer is divinyl adipate; The electrolyte consists of a lithium salt and an organic solvent; The molar ratio of the tetrathiol crosslinking agent to the diene monomer is 1:3.5; The mass fraction of the photoinitiator is 1% to 10% based on the sum of the mass of the tetramercapto crosslinking agent and the diene monomer as 100%; In the mixed solution a, the concentration of the tetrathiol crosslinking agent is 0.5 mol / L.

2. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

3. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1 or 2, characterized in that: Based on the sum of the mass of the tetramercapto crosslinking agent and the diene monomer being 100%, the mass fraction of the photoinitiator is 3%.

4. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(trifluoromethanesulfonyl)imide.

5. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The organic solvent is one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate.

6. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The positive electrode material is lithium iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material or nickel-cobalt-aluminum ternary material.

7. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The specific operation of removing bubbles in the mixed solution b by the vacuuming method is: vacuuming the mixed solution b for 2 to 5 times, and vacuuming to -0.08 MPa to -0.1 MPa each time.

8. The in-situ synthesized high-voltage resistant gel polymer electrolyte according to claim 1, characterized in that: The photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; The mass fraction of the photoinitiator is 3%, based on the sum of the mass of the tetramercapto crosslinking agent and the diene monomer being 100%; The lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(trifluoromethanesulfonyl)imide; the organic solvent is composed of two of ethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate in a volume ratio of 1:1; and the concentration of the lithium salt in the electrolyte is 1 mol / L; The positive electrode material is lithium iron phosphate; The specific operation of removing bubbles in the mixed solution b by the vacuuming method is: vacuuming the mixed solution b for 2 to 5 times, and vacuuming to -0.08 MPa to -0.1 MPa each time.

Citation Information

Cited By

  • In-situ polymerization gel polymer electrolyte, preparation method thereof and silicon-based lithium ion battery

    CN120978187A

  • In-situ curing semi-solid gel electrolyte, lithium ion battery and preparation method of in-situ curing semi-solid gel electrolyte and lithium ion battery

    CN122224945A